What a trip, Amber Brown - Danziger, Paula; Ross, Tony (Penguin Young Readers, an imprint of Penguin Group (USA) Inc. New York, 2011)
Amber Brown and her parents go to the Poconos for two weeks with Amber's best friend, Justin, and his family. Best friends Amber Brown and Justin Daniels are taking a vacation together. There's just one problem--Justin's little brother wants to tag along. Full-color illustrations